2009
DOI: 10.4315/0362-028x-72.6.1327
|View full text |Cite
|
Sign up to set email alerts
|

Limited Surveillance of Fumonisins in Brown Rice and Wheat Harvested in Japan

Abstract: Fumonisins are mycotoxins mainly produced by Fusarium verticillioides, which is a major contaminant of corn. However, there are sporadic reports of fumonisin contamination in wheat worldwide. The rice adherent fungus Gibberella fujikuroi is taxonomically closely related to F. verticillioides. Therefore, the potential risk of fumonisin contamination in rice and wheat is significant. Previously, a sensitive detection method utilizing liquid chromatography with tandem electrospray mass spectrometry (LC-ESI-MS-MS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 30 publications
(43 reference statements)
0
7
0
2
Order By: Relevance
“…In Argentina, corn and corn products showed different levels of contamination according to the region from which the samples were collected. Several studies worldwide have reported fumonisins in different crops and foods including rice, sorghum, mung beans, asparagus, black tea, cereals and animal feedstuff . There is also evidence of fumonisin contamination in wheat grains and wheat-based products. Shephard et al reviewed many of the reports on fumonisins in wheat and concluded that careful evaluation of the analytical methods and possible sources of contamination, as well as confirmation by appropriate and validated methods, is required in order to prevent the reporting of false positive results. However, low fumonisin levels in wheat grain and wheat-based foods in Italy, Spain and Japan have been reported and documented by liquid chromatography–mass spectrometry with selected ion monitoring. ,, …”
Section: Introductionmentioning
confidence: 99%
“…In Argentina, corn and corn products showed different levels of contamination according to the region from which the samples were collected. Several studies worldwide have reported fumonisins in different crops and foods including rice, sorghum, mung beans, asparagus, black tea, cereals and animal feedstuff . There is also evidence of fumonisin contamination in wheat grains and wheat-based products. Shephard et al reviewed many of the reports on fumonisins in wheat and concluded that careful evaluation of the analytical methods and possible sources of contamination, as well as confirmation by appropriate and validated methods, is required in order to prevent the reporting of false positive results. However, low fumonisin levels in wheat grain and wheat-based foods in Italy, Spain and Japan have been reported and documented by liquid chromatography–mass spectrometry with selected ion monitoring. ,, …”
Section: Introductionmentioning
confidence: 99%
“…The most important fumonisins (FUMs) are FB 1 , fumonisin B 2 (FB 2 ), and fumonisin B 3 (FB 3 ), which are predominantly produced by F. verticillioides, F. proliferatum, F. anthophi lum, and F. nygamai (Yazar and Omurtag, 2008). FUMs are usually present in maize and maize products, but they also can be found in wheat and non-corn based foodstuffs (Cirillo et al 2003;Kushiro et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…11 For human-consumed rice, the rice husks are removed, and FUM is not detected in the edible brown rice. 12 However, when rice is used to feed ruminants, the husks are not separated from the head, and stems and leaves are included in the fodder. Therefore, the risks of mycotoxin-contaminated rice in livestock fodder differ from those of rice cultivated for human consumption.…”
Section: ■ Introductionmentioning
confidence: 99%